Rearrange:

Rearrange the equation by subtracting what is come the ideal of the equal authorize from both sides of the equation : 11*(n-1)+35-(3*n)=0

Step by step solution :

Step 1 :

Equation at the end of action 1 :

(11 • (n - 1) + 35) - 3n = 0

Step 2 :

Step 3 :

Pulling out like terms :3.1 pull out favor factors:8n + 24=8•(n + 3)

Equation in ~ the end of step 3 :

8 • (n + 3) = 0

Step 4 :

Equations which are never ever true:4.1Solve:8=0This equation has actually no solution. A a non-zero constant never equates to zero.

Solving a solitary Variable Equation:4.2Solve:n+3 = 0Subtract 3 native both political parties of the equation:n = -3

One equipment was discovered :

n = -3




You are watching: Solve for n. 11(n – 1) + 35 = 3n

Why discover this

*

Terms and also topics

*

Related links

*

abc
a
x
y
/
|abs|
( )
7
8
9
*
4
5
6
-
%
1
2
3
+
0
,
.
=
abc
a
b
c
d
e
f
g
h
i
j
k
l
m
n
o
p
q
r
s
t
u
v
w
x
y
z

.
*



See more: The Usual Starting Point For Preparing A Master Budget Is Forecasting Or Estimating

back to peak